Placental miRNAs in feto-maternal communication mediated by extracellular vesicles. (December 2020) - Morales-Prieto, Diana M.; Favaro, Rodolfo R.; Markert, Udo R.
Abstract: A complex network composed of at least 1900 microRNA (miRNA) species orchestrates the development and function of the human placenta. These molecules regulate genes and pathways operating major functional processes in trophoblast cells such as proliferation, invasion, differentiation, and metabolism. Nevertheless, the cellular localization and role of most placental miRNAs remain to be determined. The existence of eutherian- (C14MC) and primate-specific miRNA clusters (C19MC), together with human placenta-specific miRNAs, indicate the relevance of these molecules in evolution and diversification of the placenta, including the acquisition of its unique features in humans. They may be related also to diseases that are exclusively present in primates, such as preeclampsia. Changes in the miRNA expression profile have been reported in several placental pathologies. Which miRNAs are involved in the pathomechanism of these diseases or act to maintain placental homeostasis is uncertain. Placenta-derived miRNAs are packed into extracellular vesicles (EVs) and distributed through the maternal circulation to distant organs, where they contribute to adaptations required during pregnancy. Similarly, the placenta also receives molecular information from other tissues to adapt fetoplacental metabolic demands to the maternal energetic supply. These processes can be impaired in pathologic conditions. Therefore, the collection of circulating placental miRNAs constitutes potentially a minimally-invasive approach to assess the fetoplacental status and to diagnose pregnancy diseases. Future therapies may include manipulation of miRNA levels for prevention and treatment of placental complications to protect maternal health and fetal development. Highlights: Placental miRNAs are transported via EVs to distant maternal cells and organs. The placental miRNA expression profile is altered in pregnancy complications. Maternal immune cells are potential targets for placental EVs and miRNA. Gene expression and functions of target cells are influenced by trophoblastic EBs.